2018
DOI: 10.3329/bjas.v46i3.36312
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy and protein supplementation on growth and nutrient requirement estimation in crossbred bull calf

Abstract: This study was carried out to investigate the effects of supplying different levels of energy and protein on the growth performance and nutrient requirements estimation in crossbred bull calves. Feeding trial was conducted for 60 days with 12 numbers of crossbred bull calves. The animals were divided into four groups i.e. T0, T1, T2and T3. Four levels of metabolizable energy (ME) and digestible crude protein (DCP) were supplied respectively in four dietary groups, T0=17.4 MJ/d and 85 g/d as maintenance ration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Present findings go with Barua et al (2008) who reported significant (P<0.05) boost in feed conversion efficiency among the dietary groups supplementing higher level of protein that was @ 15, 20 and 25 % CP over the control group. Similarly, Akhter et al (2017) reported improved dry matter conversion efficiency (58.53 to 10.00), protein conversion efficiency (4.39 to 0.92) and energetic efficiency (404.65 to 65.91 MJ MEI/kg body weight gain) on feeing nutrient dens (protein and energy) diet in crossbred (Indigenous x 50% Holstein Friesian) bull calves. In contrary to modern research, Previous works of Umunna et al (1980) revealed that increase in protein levels after a certain level declined the feed conversion and Greathouse et al (1974) reported higher rate of feed conversion due to rising of protein level without concurrent rising of energy value of diet.…”
Section: Feed Conversion Efficiency and Economicsmentioning
confidence: 84%
See 2 more Smart Citations
“…Present findings go with Barua et al (2008) who reported significant (P<0.05) boost in feed conversion efficiency among the dietary groups supplementing higher level of protein that was @ 15, 20 and 25 % CP over the control group. Similarly, Akhter et al (2017) reported improved dry matter conversion efficiency (58.53 to 10.00), protein conversion efficiency (4.39 to 0.92) and energetic efficiency (404.65 to 65.91 MJ MEI/kg body weight gain) on feeing nutrient dens (protein and energy) diet in crossbred (Indigenous x 50% Holstein Friesian) bull calves. In contrary to modern research, Previous works of Umunna et al (1980) revealed that increase in protein levels after a certain level declined the feed conversion and Greathouse et al (1974) reported higher rate of feed conversion due to rising of protein level without concurrent rising of energy value of diet.…”
Section: Feed Conversion Efficiency and Economicsmentioning
confidence: 84%
“…These findings correlate with Barua et al (2008) who reported higher dry matter and nutrient intake with high levels of protein in Red Chittagong heifers. Similarly Akhter et al (2017) reported improvement in intake of crude protein, digestible crude protein and energy intake of crossbred (Indigenous x 50% Holstein Friesian) bull calves on feeding dense (protein and energy) diet whereas dry matter intake was without effect. Zhang et al (2017) reported similar value of dry matter intake (6.3 kg/day) of Holstein heifers on feeding isocaloric diet with low, medium and high protein diet (10.2, 11.9, and 13.5%, respectively) and difference amongst treatments were non-significant due to restricted feeding.…”
Section: Dry Matter and Nutrients Intakementioning
confidence: 93%
See 1 more Smart Citation